Isotopes and innovation : MDS Nordion's first fifty years, 1946-1996 - Litt, Paul (McGill-Queen's University Press, 2000)
When radium began to be used as a cancer treatment, Eldorado quickly became familiar with the medical marketplace and adept at developing products that could solve clinical problems and, more important, save lives. When Canadian nuclear reactors at Chalk River began producing radioisotopes that outperformed radium, Eldorado's radium sales department was transferred to a new crown corporation, Atomic Energy of Canada Limited, created to manage Canada's nuclear research establishment. The new company developed many useful applications for radioisotopes, including cobalt-60 cancer therapy machines and industrial sterilization plants. Bought by Medical Data Services Inc. in the early 1990s, MDS Nordion was a runaway success, creator and sole proprietor of several market-leading products. Isotopes and Innovation describes how a company capitalized on the byproducts of Canada's unique nuclear research program to attain a commanding international position in extremely specialized and demanding high-tech markets, a saga in which innovative research and enterprising global marketing have brought commercial success and saved countless lives around the world.